Penerapan Metode Trend Moment dalam Prediksi Stok Produk pada PT. Indomarco Prismatama Cabang Ngesrep - Mahfudz Aditya; Ahir Yugo Nugroho (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
PT. Indomarco Prismatama is a retail company with the main activity of selling various types of products. However, in its operational process, obstacles often arise, especially in the input stage of transaction data for incoming and outgoing goods. These recording errors often result in differences between the stock recorded in the system and the number of products actually available in the warehouse. The company faces problems with stock shortages on several products that should be available for sale to customers, resulting in hampered sales processes, and sales targets cannot be realized optimally. There is also often a buildup of product stock in the warehouse, resulting in products expiring, which impacts losses for the company. This study applies the Trend Moment method. The Trend Moment method is an analysis technique used to observe the upward or downward trend of data within a certain time span. The trend pattern is calculated based on the average change that occurs from period to period, so it can illustrate the direction of data development in the long term. The application used in making predictions is the Active Server Page (ASP) programming language, which is considered more efficient in terms of system maintenance and runs the system with an SQL Server R2 database.